Assessing the independent and combined effects of subsidies for antimalarials and rapid diagnostic testing on fever management decisions in the retail sector: results from a factorial randomised trial in western Kenya. Issue 2 (28th September 2016) - Prudhomme O'Meara, Wendy; Mohanan, Manoj; Laktabai, Jeremiah; Lesser, Adriane; Platt, Alyssa; Maffioli, Elisa; Turner, Elizabeth L; Menya, Diana
Abstract : Objectives: There is an urgent need to understand how to improve targeting of artemisinin combination therapy (ACT) to patients with confirmed malaria infection, including subsidised ACTs sold over-the-counter. We hypothesised that offering an antimalarial subsidy conditional on a positive malaria rapid diagnostic test (RDT) would increase uptake of testing and improve rational use of ACTs. Methods: We designed a 2×2 factorial randomised experiment evaluating 2 levels of subsidy for RDTs and ACTs. Between July 2014 and June 2015, 444 individuals with a malaria-like illness who had not sought treatment were recruited from their homes. We used scratch cards to allocate participants into 4 groups in a ratio of 1:1:1:1. Participants were eligible for an unsubsidised or fully subsidised RDT and 1 of 2 levels of ACT subsidy (current retail price or an additional subsidy conditional on a positive RDT). Treatment decisions were documented 1 week later. Our primary outcome was uptake of malaria testing. Secondary outcomes evaluated ACT consumption among those with a negative test, a positive test or no test. Results: Offering a free RDT increased the probability of testing by 18.6 percentage points (adjusted probability difference (APD), 95% CI 5.9 to 31.3). An offer of a conditional ACT subsidy did not have an additional effect on the probability of malaria testing when the RDT was free (APD=2.7; 95% CI −8.6 to 14.1). However, receiving the conditional ACT subsidy increased the probability of taking an ACT following a positive RDT by 19.5 percentage points (APD, 95% CI 2.2 to 36.8). Overall, the proportion who took ACT following a negative test was lower than those who took ACT without being tested, indicated improved targeting among those who were tested. Conclusions: Both subsidies improved appropriate fever management, demonstrating the impact of these costs on decision making. However, the conditional ACT subsidy did not increase testing. We conclude that each of the subsidies primarily impacts the most immediate decision. Trial registration number: NCT02199977 .